Sex effects on dynamic structure–function coupling of intrinsic brain network - Zhang, Xi; Li, Dandan; Yuan, Yuting; Han, Xuebing; Yang, Lan; Lu, Jiayu; Li, Ting; Li, Zhifeng; Wang, Bin (Brain imaging and behavior, 2025)
Sex differences in static structure–function coupling between structural connectivity (SC) and functional connectivity (FC) have been documented. However, the human brain is highly dynamic, and static coupling fails to capture the time-varying properties of neural activity. It remains unclear how sex influences dynamic SC-FC coupling over time. Moreover, intrinsic functional networks represent a core feature of brain organization. Here, we quantified sex differences in dynamic FC strength and SC-FC coupling at the intrinsic functional network level using a sliding window approach. Using two window sizes (50 TRs and 30 TRs), we constructed dynamic FC networks and identified hyper-connected and hypo-connected states via k-means clustering. The results showed females performed higher whole-brain SC-FC coupling in hyper-connected state. Specifically, females exhibited higher FC strength and coupling in systems related default mode network in this state. In addition, females exhibited higher FC strength and coupling in systems related limbic/paralimbic and subcortical network in hypo-connected state. Males exhibited higher FC strength and coupling in systems related somatosensory/motor and auditory network in hyper-connected state. Finally, sex-specific patterns in correlations were shown between SC-FC coupling and cognitive performance in distinct states. This study provides new insights into sex-related effects on the neurodevelopmental basis of cognitive function through the perspective of dynamic SC-FC coupling.